Doing business 2010. (Palgrave Macmillan, 2009)
Doing Business 2010 is the seventh in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 183 economies--from Afghanistan to Zimbabwe--and over time. Regulations affecting 10 stages of a business's life are measured: starting a business, dealing with construction permits, employing workers, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforci.